The Specialized school in time of inclusion - Santos, Roseli Albino dos (2014)
This study has the objective to investigate the meanings about school inclusion and disability, produced by a group of professionals engaged in a specialized school located in a city in the state of São Paulo. The metodology used was semi-structured and structured interviews with the director of the institution, two pedagogical coordinators and five teachers. Data were subjected to a descriptive-interpretative analysis. The results indicated that professionals attribute the responsibility for self development, only to students with intellectual disabilities . The emphasis of the speeches falls on the inability of the student and the immutability of disability. It is observed that the narratives do not reveal critical positioning of professional educational processes involving this population. The professionals who work in specialized institution still have a conception of disability based on the inability of the student and, despite defending the right of these students to school inclusion, these professionals still manifest fear of what they will find outside the walls of the institution, revealing attitudes and overprotection ignorance of the role of specialized institution in times of inclusion. We conclude that the conceptions about intellectual disability and inclusive education presented by professionals can contribute much more to the reiteration of school exclusion, historically focused on this population than for its actual inclusion in the school system of education.